Effect of Placental Cryoextract on Superovulation Induction in Mice with Chronic Ovary Inflammation - Grischenko, N. G.; Grischenko, V. I.; Smolyaninova, E. I.; Chernyshenko, L. G.; Volkova, N. A. (Problems of Cryobiology and Cryomedicine, 2010)
The effect of placental cryoextract (PC) on the results of superovulation in laboratory mice with syndrome of chronic ovary inflammation was studied. It is shown that chronic ovary inflammation in mice females affects significantly the results of superovulation. The quantity of oocytes, zygotes and 2-cell embryos as well as morphologic quality of the embryos decrease significantly. PC administration in the animals manifests pronounced therapeutic action and promotes more effective superovulation under exogenous gonadotropic hormones administration The increase in the total number of gametes and early embryos was found. It was also found that the morphology of gametes and early embryos after application of CP improved signisicantly.